Resisting or Adapting? How Private Catholic High Schools in Quebec Respond to State Secularism and Religious Diversification - Martínez-Ariño, Julia; Lefebvre, Solange (Eurostudia)

(untitled) (Le Centre canadien d’études allemandes et européennes, 2016)
The education system in Quebec has found itself at the center of the debates about secularism since the 1960s. Embedded in broader academic debates about processes of secularization and deconfessionalization of state institutions, religious diversification of society, and reconfiguration of Catholicism, this article aims to analyze how private Catholic schools in post-Catholic Quebec respond to the challenges posed by the secularizing pressures of the state, and the religious diversification of their target populations. Based on a qualitative case study conducted in two private-partially-publicly-funded Catholic or Catholic-oriented high schools (one Anglophone, one Francophone) in Quebec, we argue that the different approaches observed result from the different processes of internal secularization that these two schools have gone through. We draw on Steve Bruce’s notion of “cultural defense” and David Martin’s conceptualization of different trajectories of secularization to interpret these results.